Evaluation of Low-Dose 3D Skull CT Images in Craniosynostosis - Fariba Zarei; Zeynab Mashayekhi; Vani Vardhan Chatterjee; Sabysachi chatterjee; Rezvan Ravanfar Haghighi (Iranian Journal of Medical Physics, 2022)
Introduction: Computed Tomography (CT) is nowadays used widely to differentiate normal brain cranium sutures from abnormal ones in pediatric patients with the aim of early treatment. This study tried to develop a low-dose CT protocol with the acceptable image quality of skull bone in order to evaluate craniosynostosis.Material and Methods: In this study a cranium bone of human cadaver was scanned with standard and reduced dose protocols. Two radiologists verified the quality of skull bone images acquired from the protocol in which there had been 60% dose reduction to scan pediatric patients. The quality of low dose protocol of three dimensional (3D) CT images of skull bone of 57 pediatric subjects suspected of craniosynostosis were compared with standard-dose skull CT images of 44 patients of the same age range. Volume CT dose index (CTDIvol), dose-length product (DLP), and effective dose (ED) were used to evaluate CT dose protocols. The comparison was made by two sample t-test.Results: Mean and standard deviations of CTDIvol, DLP, and ED of standard and reduced doses were 12.4±2.7 mGy, 191.5±54 mGy.cm, 1.94±0.58 mSv and 5.4±0.2 mGy, 85±9 mGy.cm, 0.77±0.17 mSv, respectively, which had statistically significant difference (α=0.05). The quality of skull bone views obtained from low-dose CT protocol were found to be as good as in standard dose. Conclusion: Standard-dose 3D CT protocol of skull bone can be replaced by a 60%-reduced-dose 3D CT protocol with comparable image quality in pediatric patients suspected of craniosynostosis.